(untitled) (REMUNOM, 2024)
Eating, as a way of exploring and experiencing the world, is a complex skill that encompasses numerous factors such as parental relationships, personal preferences, life stage, family eating habits, health conditions, sociocultural context, developmental level, orofacial aspects, and also sensory processing. This study investigates the relationship between food selectivity and sensory integration dysfunctions in an individual. It is a qualitative case study conducted through clinical observations and interviews, identifying eating behavior patterns that reflect sensory challenges. Results: The onset of food selectivity was identified as stemming from sensory integration dysfunctions. Following stimuli and regulation, the first signs of food acceptance were observed. Conclusion: Further studies are needed to confirm this link between dysfunction and food selectivity.